2013
DOI: 10.1186/1471-2393-13-160
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Folic acid supplementation, dietary folate intake during pregnancy and risk for spontaneous preterm delivery: a prospective observational cohort study

Abstract: BackgroundHealth authorities in numerous countries recommend periconceptional folic acid to pregnant women to prevent neural tube defects. The objective of this study was to examine the association of folic acid supplementation during different periods of pregnancy and of dietary folate intake with the risk of spontaneous preterm delivery (PTD).MethodsThe Norwegian Mother and Child Cohort Study is a population-based prospective cohort study. A total of 65,668 women with singleton pregnancies resulting in live … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…Other studies did not explore this association by duration of maternal supplementation. Consistent with several earlier studies [22,23,27], but not all [17,20,29,30], we found that higher dietary folate intake during pregnancy was associated with reduced risk of PB and certain subtypes. We did not observe a synergistic effect between dietary folate and folic acid supplements.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Other studies did not explore this association by duration of maternal supplementation. Consistent with several earlier studies [22,23,27], but not all [17,20,29,30], we found that higher dietary folate intake during pregnancy was associated with reduced risk of PB and certain subtypes. We did not observe a synergistic effect between dietary folate and folic acid supplements.…”
Section: Discussionsupporting
confidence: 93%
“…Earlier epidemiological studies investigating the associations between PB and folic acid supplements/dietary folate intake have provided conflicting results [17][18][19][20][21][22][23][24][25][26][27][28][29][30]42]; among them, Dunlop et al [43] investigated plasma level of folate. While ten studies have reported a protective effect of folic acid supplements/dietary folate intake on PB [18][19][20][21][22][23][24][25][26][27], one study reported that risk of PB associated with folic acid supplement use varied by time periods of use (preconception, first trimester, and second trimester) [17] and four studies found no association [28][29][30]42]. Variations in dosage of folic acid use, selected pregnancy period of use, definitions of PB by gestational age, and lack of consideration of PB clinical subtypes among different populations might partially contribute to the inconsistent results.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, fetal and neonatal risks include prematurity, low birth weight, fetal distress which contribute to perinatal morbidity and mortality as well as infants born to Rural Pregnant Women in North Western Zone of Tigray, Ethiopia: Comparative Study anemic mothers will more likely to become anemic themselves [4,5]. Folic acid deficiency at conception and in early pregnancy is associated with increased risk of neural tube defects and other adverse pregnancy outcomes such as preeclampsia, malformations such as orofacial clefts, spontaneous abortion, fetal death, fetal growth restriction and preterm delivery [6,7]. Anemia during pregnancy is defined by the Centers of Disease Control and prevention as a hemoglobin <11g/dl [8].…”
Section: Introductionmentioning
confidence: 99%
“…Several epidemiological studies have investigated the association between folic acid supplementation and the risk of preeclampsia; however, results from these studies have been inconsistent. Three studies found that folic acid-containing multivitamins were associated with reduced risk of preeclampsia, 1416 three studies reported no association with folic acid supplement alone 17,18 and one study observed that dietary folate intake reduced the risk of preeclampsia. 19 …”
Section: Introductionmentioning
confidence: 99%